Simulation studies on electrical characteristics of silicon nanowire feedback field-effect transistors with interface trap charges - Yejin Yang (Nature Portfolio, 2021)
Abstract In this study, we examine the electrical characteristics of silicon nanowire feedback field-effect transistors (FBFETs) with interface trap charges between the channel and gate oxide. The band diagram, I–V characteristics, memory window, and operation were analyzed using a commercial technology computer-aided design simulation. In an n-channel FBFET, the memory window narrows (widens) from 5.47 to 3.59 V (9.24 V), as the density of the positive (negative) trap charges increases. In contrast, in the p-channel FBFET, the memory window widens (narrows) from 5.38 to 7.38 V (4.18 V), as the density of the positive (negative) trap charges increases. Moreover, we investigate the difference in the output drain current based on the interface trap charges during the memory operation.